2009
DOI: 10.1159/000207515
|View full text |Cite
|
Sign up to set email alerts
|

Refining the 22q11.2 deletion breakpoints in DiGeorge syndrome by aCGH

Abstract: Hemizygous deletions of the chromosome 22q11.2 region result in the 22q11.2 deletion syndrome also referred to as DiGeorge, Velocardiofacial or Shprintzen syndromes. The phenotype is variable but commonly includes conotruncal cardiac defects, palatal abnormalities, learning and behavioral problems, immune deficiency, and facial anomalies. Four distinct highly homologous blocks of low copy number repeat sequences (LCRs) flank the deletion region. Mispairing of LCRs during meiosis with unequal meiotic exchange i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 63 publications
3
47
0
Order By: Relevance
“…The deleted sizes of LCR22A-D in cases 2-9 fall into 2 subcategories, 2.57 or 2.80 Mb ( table 1 ), consistent with our previous observation in 20 individuals containing LCR22A-D deletions [Bittel et al, 2009]. These LCR22A-D deletions share the same distal breakpoints at LCR22D, but vary slightly at the proximal breakpoints within LCR22A spanning an Ïł 498-kb region encompassing PRODH, USP18, GGT3P, TSSK2, GSC2 , and multiple members of the DiGeorge syndrome critical region genes, including DGCR6 (online suppl.…”
Section: Abnormal Cnvs On Chromosome 22supporting
confidence: 91%
“…The deleted sizes of LCR22A-D in cases 2-9 fall into 2 subcategories, 2.57 or 2.80 Mb ( table 1 ), consistent with our previous observation in 20 individuals containing LCR22A-D deletions [Bittel et al, 2009]. These LCR22A-D deletions share the same distal breakpoints at LCR22D, but vary slightly at the proximal breakpoints within LCR22A spanning an Ïł 498-kb region encompassing PRODH, USP18, GGT3P, TSSK2, GSC2 , and multiple members of the DiGeorge syndrome critical region genes, including DGCR6 (online suppl.…”
Section: Abnormal Cnvs On Chromosome 22supporting
confidence: 91%
“…In all cases other than patient 15, the deletion involved the LCR22-A. All of these deletions overlapped with the proximal variable region described by Bittel et al 41 (chr22: 18 656 078-19 018 178). In contrast, the distal breakpoint was more variable; in view of our small series, no conclusions could be reached.…”
Section: Discussionmentioning
confidence: 56%
“…Four distal low copy repeats (LCR) were identified and were designated as LCR-E to LCR-H [Shaikh et al, 2007]. These LCRs appeared to be located at 22q11.2 from 20.654 to 23.215 Mb (NCBI Build 36), whereas the proximal LCRs (LCR-A to LCR-D) that are included in the common $3 Mb region, are reportedly located from 17.310 to 20.241 Mb [Jalali et al, 2008;Bittel et al, 2009]. Saitta et al [2004] and Coppinger et al [2009] suggested that LCRs on 22q11.2 mediate non-allelic homologous recombination resulting in rearrangements of 22q.…”
Section: Introductionmentioning
confidence: 99%